PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 12 PADANG - Aditha P, Indah Ramadhani (Departemen Matematika, 2023)
Math problem-solving is essential. But some students still struggle with this competence. Initial observations in class VII of SMPN 12 Padang in 2022/2023 showed low levels of this ability. This study compared the mathematical problem-solving skills of class VIII students at SMPN 12 Padang in 2023/2024 who used the Problem-Based Learning (PBL) model to the direct learning methodology. The research is quasi-experimental and descriptive with a non-equivalent posttest only control group design. Quizzes and final tests were research tools. Data analysis, including normality and hypothesis testing, shows that the PBL paradigm improves mathematical problem-solving more than the direct learning model. Keywords– Problem Solving Ability, Problem Based Learning, Direct Learning.